Nilai Moral dalam Serat Wulangreh Pupuh III: Gambuh - Prasetyo, Daniel Dwi; Sulanjari, Bambang (Universitas PGRI Semarang, 2025)
This study delves into the depth of moral values contained in Pupuh Gambuh, especially Pupuh III from Serat Wulangreh, a monumental classical Javanese literary work by Sri Susuhunan Pakubuwana IV. As an integral part of the Javanese literary treasury, this song is not just a string of words, but a reflection of rich and profound moral, ethical, and life wisdom teachings. Through a qualitative-descriptive approach combined with philological and hermeneutic methods, this study aims to uncover the implicit and explicit moral messages in the text. The analysis conducted identified a number of noble values that are still very relevant to the context of modern society. Honesty, as the main foundation of community life, is raised as the central theme. Exemplary behavior, which emphasizes the importance of imitating good behavior even though it comes from individuals who are considered lowly, demonstrates the principles of egalitarianism and moral objectivity. Humility is contrasted with the dangers of arrogance (adigung, adiguna, adigang), showing how important a humble attitude is to avoid self-destruction. These values are not only limited to moral teachings, but also a reflection of Javanese local wisdom which is rich in humanist values. The research contributes significantly to the reinterpretation of Javanese local wisdom values in the context of character education development. By analyzing Pupuh III Serat Wulangreh in depth, this research is expected to provide new insights into how these noble values can be implemented in everyday life. The implementation of these values is believed to be able to enrich the nation's character education treasury, forming a young generation with noble character and able to face the challenges of morality in the modern era. The results of this study are expected to be a reference for the development of a character education curriculum based on local wisdom values, while preserving the nation's valuable cultural heritage.